A near-infrared turn-on probe for in vivo chemoselective photoacoustic detection of fluoride ion. (June 2019) - Zeng, Leli; Yuan, Yanyan; Jiang, Chao; Mu, Jing; Li, Fan; Wan, Yilin; Xu, Han; Qu, Junle; Huang, Peng; Lin, Jing
Abstract: The detection of fluoride ion (F − ) in living subjects is of value for healthcare and environmental fields. Here, a near-infrared (NIR) turn-on photoacoustic (PA) probe composed of naphthalimide unit, namely LET-1, was developed for chemoselective photoacoustic detection (PAD) of F − . The response and mechanism of the interaction between F − and LET-1 were evaluated through kinetic optical studies, 1 HNMR spectra analysis and docking calculations. The results demonstrated that LET-1 could rapidly recognize F − with good selectivity and high sensitivity. Upon the interaction with F −, this non-photoacoustic LET-1 probe could produce a turn-on PA signal at 680 nm, which was used as an indicator for PAD of F − in living subjects, such as soybean sprout and mouse. The present study provides a new approach for in vivo chemoselective PA detection of anions. Highlights: The probe is applied in anion detection using photoacoustic imaging technique. The probe is a near-infrared turn-on photoacoustic probe. The probe can monitor the content of fluoride ions (F − ) in living plant and animal.